The Implementation of Telegram in Reading Class to Improve Students’ Skimming and Scanning Skills - Muhammad Syaiful, Jihad (Elsya : Journal of English Language Studies, 2023)
Skimming and scanning are important reading strategies that allow individuals to quickly gather information from written materials. With the advance of digital communication platforms, like Telegram improving students' scanning and skimming skills has become increasingly relevant. While the utilization of technological resources in reading and teaching English has been examined in different settings, there is a need to investigate the potential of Telegram as a specific tool for enhancing skimming and scanning abilities. This research uses both quantitative and qualitative data collection methods. The respondents in the research are 40 English major learners. The protocols to gather the data were questionnaires and interviews. The study suggests that utilizing Telegram can help students to improve their motivation and engagement, which can further enhance the learning process. Exploring the future implications of employing Telegram requires more investigation, especially for skimming as well as scanning development, as well as its incorporation across different age groups and academic contexts. Nonetheless, the results of the research offer insightful information into the integration of digital communication platforms as effective tools for improving reading strategies, paving the way for innovative approaches to enhance literacy skills in the digital era.